Novel methods for the detection of glutathione by surface-enhanced Raman scattering: A perspective review - Mohammad Kamal Hossain; Genin Gary Huang; Mohammad Mozahar Hossain (Heliyon)
Detection of biomolecules, Glutathione (GSH) in particular, is important because it helps assess antioxidant capacity, cellular protection, detoxification processes, and potential disease associations. Monitoring glutathione levels can provide valuable information about overall health and well-being. Many medical disorders have been connected to glutathione levels. Higher glutathione levels have been seen in several cancer cell types, which may increase their resistance to radiation and chemotherapy. Glutathione levels can be measured through various methods, such as colorimetric assays and fluorescent probes. However, surface-enhanced Raman scattering (SERS) has been known as an efficient and selective technique for biomolecule detection. Here in this perspective review, we have reported two distinctive methods based on SERS technique in detection of GSH; heat-induced method and reversed reporting agent method. Several variables that can impact the detection scheme were elaborated in the ''heat-induced method,'' including pretreatment, nanoparticle reduction time, the process temperature, the pH of the colloidal solution, the concentration of citrate buffer, and the concentration of participating nanoparticles. To choose the best reporting agent for a reverse reporting scheme using SERS approaches, several reporting agents were examined in the second method. In order to grasp the situation at hand, biomolecule detection—specifically, GSH detection schemes—was briefly discussed. SERS spectroscopy and its associated terminology were then covered followed by the perspective and outlook of GSH detection at the end. To meet the demands of real-time applications in everyday life and to enhance SERS methods for biomolecule detection—in particular, GSH detection—such a thorough investigation is unavoidable.